MANAJEMEN KEUANGAN PRIBADI PADA SISWA MATTAYOM DI SEKOLAH SANGKOM ISLAM WITTAYA SCHOOL - Siregar, Rini; Poham, Selamat (Hijri, 2024)
This research aims to analyze the practices of personal financial management among Mattayom students at Sangkom Islam Wittaya School. The research employed survey and interview methods with Mattayom class students, along with qualitative analysis. Findings reveal that a significant number of Mattayom students have limited understanding of personal financial management. Despite receiving regular allowances, a lack of awareness regarding the importance of budgeting and saving makes them vulnerable to financial instability. Educational factors, spending patterns, and social influences also contribute to students' financial management practices. Therefore, this research recommends the development of an integrated financial education program within the school curriculum. It is expected to assist Mattayom students in enhancing their personal financial management skills and preparing them to face future financial challenges